2020
DOI: 10.37358/rc.20.7.8225
|View full text |Cite
|
Sign up to set email alerts
|

An Eco-Friendly Solution for the Efficient Elimination of Pentoxifylline from Water: An Operational Performance Investigation

Abstract: In recent years, more and more pollutants (including pharmaceuticals, personal care products, pesticides, herbicides, hormones, chemicals) are detected in the aquatic environment. Even if they are encountered in very low concentrations, the toxicological data reveal that they represent a major risk both for the water living organisms and for human beings. Moreover, an important resistance to the classical methods applied at wastewater treatment plants characterizes them. Aeration, coagulation, flocculation, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…It was found that the CA removal in the absence of catalyst is of only less than 9% after 60 min and 17% after an exposure time of 180 min. Similar results were previously reported in other papers [45][46][47].…”
Section: Effects Of Some Operating Conditions On the Clofibric Acid Elimination With Zn4la400supporting
confidence: 93%
“…It was found that the CA removal in the absence of catalyst is of only less than 9% after 60 min and 17% after an exposure time of 180 min. Similar results were previously reported in other papers [45][46][47].…”
Section: Effects Of Some Operating Conditions On the Clofibric Acid Elimination With Zn4la400supporting
confidence: 93%